Pengaruh Word Of Mouth (WOM), Kualitas Produk Dan Harga Terhadap Minat Beli Konsumen Nesia Cake Palembang - Desi Rama Yuni; Komariah Hildayanti; Mohammad Kurniawan DP (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
This study aims to analyze the influence of Word of Mouth (WOM), Product Quality and Price on consumer purchasing interest in Nesia Cake Palembang. The research method used is a descriptive quantitative approach with data collection techniques through distributing questionnaires to 99 consumers. The data obtained were analyzed using multiple linear regression analysis with the help of SPSS version 27. The results showed that Word of Mouth (WOM), Product Quality and Price had a positive and significant effect on consumer purchasing interest. The regression equation obtained was Y = 3.163 + 0.189 X1 + 0.226 X2 + 0.345 X3 + e. The results of the partial test (t test) showed that Word of Mouth (WOM) had a positive and significant effect on consumer purchasing interest with a t-value of 2.096, Product Quality had a t-table value of 1.98, while price had a t-value of 3.336, all of which were greater than the t-table of 2.70, and had a significance of less than 0.05. Furthermore, the results of the simultaneous test (F test) show a calculated F value of 124.196, greater than Ftable 2.70, which means that the three independent variables together have a positive and significant effect on consumer purchasing interest. The coefficient of determination (Adjusted R Square) value of 0.790 indicates that 79.0% of the variation in consumer purchasing interest can be explained by Word of Mouth (WOM), Product Quality and Price, while the rest is influenced by other factors outside this study. Thus, it can be concluded that increasing Word of Mouth (WOM), Product Quality and Price are important factors in increasing consumer purchasing interest.